Corporate Social Responsibility Practices and Their Impact on the Community : A Case Study of Ambuja Cement Ltd. - Kumari, Santosh; Sehrawat, Anil; Sharma, Tanu (Prabandhan: Indian Journal of Management, 2017)
This paper analyzed the different kind of CSR practices adopted by Ambuja Cement Ltd. in relation to local community and measured the impact of CSR practices on the local community. To fulfill this objective, the perceptions and expectations of the community were taken on company’s corporate social responsibility practices by conducting focus group discussions and through a structured questionnaire. The sample included the most educated member of each family in the community. The mining area of Ambuja Cement plant was also considered while collecting responses on perceptions and expectations of CSR. The impact of CSR activities was assessed qualitatively and quantitatively.